2011
DOI: 10.1002/lary.21848
|View full text |Cite
|
Sign up to set email alerts
|

Persistent positional nystagmus

Abstract: Involvement of the superior semicircular canal (SSC) in benign paroxysmal positional vertigo (BPPV) is rare. SSC BPPV is distinguished from the more common posterior semicircular canal (PSC) variant by the pattern of nystagmus triggered by the Dix-Hallpike position: down-beating torsional nystagmus in SSC BPPV versus up-beating torsional nystagmus in PSC BPPV. SSC BPPV may be readily treated at the bedside, which is a key component in excluding central causes of down-beating nystagmus. We present an unusual vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…ASC-BPPV is an uncommon diagnosis. Our study showed an incidence of 0.6% while Heidenreich KD et al found it to be between 1% and 3%28 and Casani AP et al quoted an incidence between 2% and 21%.29 It can occur following a canal switch, where the debris exits the PSC via the common crus into the ASC. Refractory cases occur when debris lodge on the ampullated ends of the ASC, near the cupula.…”
Section: Uncommon Bppv Variantsmentioning
confidence: 43%
“…ASC-BPPV is an uncommon diagnosis. Our study showed an incidence of 0.6% while Heidenreich KD et al found it to be between 1% and 3%28 and Casani AP et al quoted an incidence between 2% and 21%.29 It can occur following a canal switch, where the debris exits the PSC via the common crus into the ASC. Refractory cases occur when debris lodge on the ampullated ends of the ASC, near the cupula.…”
Section: Uncommon Bppv Variantsmentioning
confidence: 43%